Critical ivestigation on adoption of e-business towards Malaysian organizational perspective - Haque, A. K. M. Ahasanul; Torafder, Arun Kumar; Yasmin, Farzana; Nikhashemi, Seyed Rajab (TextRoad Publication, 2012)
The aim of this paper is to investigate factors affecting adoption of e-business among Malaysian organizations. A research framework was developed to testify the statistical relationships among influencing factors and e-business adoption. Factor analysis was performed to extract to decide the number of factors underlying assess of measured variables of interest. Structural equation model (SEM) was tested to anticipate the effects of the explanatory variables. This study showed that four out of five adoption factors have significant impact on e-business adoption. These factors are relative advantage, complexity, compatibility and observability. Moreover, results showed that trialbility has no significant effect on e-business adoption. This study offered an insight into e-business adoption, which has not previously been investigated and at the same time, statistical tests significance makes this study a potential cornerstone for future research.